Using RGB-D Cameras in Live Action Visual Effects - Kruse, Jan (Auckland University of Technology, 2016)
Film production greatly depends on digital visual effects to combine live action images and computer generated elements. The introduction of Deep Compositing streamlines the integration workflow of rendered computer images. This new technique relies on depth information, which is the distance between any objects in the scene and the camera itself. While depth data is available as a byproduct in computer generated images, live action camera files lack this kind of information. Only the recent arrival of a new generation of devices called RGB-D cameras, has enabled researchers and filmmakers to conduct first experiments with depth data in conjunction with live action images. The consistent acquisition of distance information and color pictures might allow for workflow improvements in live action visual effects similar to what has been demonstrated with Deep Compositing in conjunction with rendered computer images. This research is investigating the impact of RGB-D devices on established live action visual effects workflows. RGB-D images are used for effective CG placement, and a proof of concept workflow has been implemented. Findings related to quality, resolution and range of acquired images have been documented and discussed, and suggestions for future improvements of devices and workflows have been made.
Keywords: Visual effects; RGB-D cameras